RESPONSIBILITAS SUKU DINAS PERTAMANAN DAN HUTAN KOTA DALAM PEMELIHARAAN RUANG TERBUKA HIJAU TAMAN PUBLIK DI KECAMATAN DUREN SAWIT JAKARTA TIMUR - Virginia Destanaya Alma Cantika; Dyah Lituhayu; Titik Djumiarti (Journal of Public Policy and Management Review, 2023)
Green Open Space public parks are important to provide in the city area because as a center of physical fitness and fitness for sports facilities, natural recreation, and beautifying the environment. Therefore it is important to maintain and maintain the park environment so as not to experience a decrease in the quality of the park and maintain the quality of the environment that is already good. Maintenance in public parks in Duren Sawit Subdistrict is the responsibility of the East Jakarta Parks and Urban Forest Service. This study aims to analyze the responsibilities of the Park and Urban Forest Service Tribe according to Cooper which consists of objective and subjective responsibility and analyze the supporting and inhibiting factors for the responsibilty of the Park and Urban Forest Service Tribe in maintaining public parks in Duren Sawit District. The research method used is descriptive qualitative with data collection techniques, namely observation, interviews, and documentation. The results showed that the responsibilty of the Parks and Urban Forests Service in maintaining public parks was still not optimal because there were factors, namely the lack of the number of park maintenance workers, the lack of the number and quality of work equipment was not sufficient, the budget to carry out park maintenance was still insufficient, this was due to facilities in several parks that were still damaged due to the actions of less responsible residents, but on the other hand there were still a small number of residents who cared about maintaining the park.